PEMBELAJARAN KITAB KUNING DI PESANTREN - Kholis, R. Ahmad Nur; Mujiharto; Karom, Luqman Ahsanul (Jurnal Studi Pesantren, 2024)
Learning in pesantren can be classified into 4 (four) levels. Within each of these levels the fields of study and the basis for learning the kitab kuning are different. At elementary level pesantren, the field of study is focused on procedures for reading the Qur'an and daily prayers as well as reading in prayer. Learning at this level is given on a skill-based basis. In pesantren at secondary level I, learning is focused on the study of Arabic grammar (nahwu and sharraf). Similar to the previous level, in this phase learning is carried out on a skill-based basis. At secondary level II pesantren, the learning material provided is a study of the kitab kuning across fields. Learning at this level is carried out based on content understanding. At high-level pesantren, students are given more specific subject matter. Learning at this level is in-depth and based on constructivism where students are encouraged to think critically and can understand the epistemological conceptual framework of the author of the kitab kuning. Keywords: Kitab Kuning, Pesantren